Impact of flavor-changing neutral current top quark interactions on BR(t -> bW) - Ferreira, P. M. (2012)
We study the effect that flavor-changing neutral current interactions of the top quark will have on the branching ratio of charged decays of the top quark. We have performed an integrated analysis using Tevatron and B-factories data and with just the further assumption that the Cabibbo-Kobayashi-Maskawa matrix is unitary, we can obtain very restrictive bounds on the strong and electroweak flavor-changing neutral current branching ratios Br(t -> qX)< 4.0x10(-4), where X is any vector boson and a sum in q=u, c is implied.